Analisis Dasar Kualifikasi Perbuatan Melanggar Hukum dalam Sengketa Pembatalan Polis Asuransi Jiwa secara Sepihak : Studi Putusan Nomor 5871 K/Pdt/2024 - Salsabila Jasmine Briliana Putri; Arief Suryono (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2026)
The purpose of this study is to analyze the legal basis for the qualification of unlawful acts in disputes concerning the unilateral cancellation of life insurance policies by the insurer as reflected in Decision Number 5871 K/Pdt/2024. This research is a normative legal study with a prescriptive nature, employing both case and statutory approaches. The legal materials used in this study consist of primary and secondary legal materials which are analyzed qualitatively using the syllogistic method with deductive reasoning. The results of the study indicate that the qualification of an unlawful act in the a quo decision is based on a systematic interpretation of Article 1338 of the Indonesian Civil Code, which is understood in relation to the binding source of agreements under Article 1339 of the Indonesian Civil Code. Furthermore, the existence of naturalia elements also emphasizes the presence of legal obligations inherent in an agreement even though they are not explicitly stated therein. In life insurance, the obligation to pay claims after the insured risk has occurred constitutes a normative consequence inherent in the policy; therefore, the unilateral cancellation of a life insurance policy fulfills the elements of an unlawful act as stipulated in Article 1365 of the Indonesian Civil Code.